Appraise the cognitive alertness of night shift worker: case of bottling company operators in central Northern Nigeria (2023)
Night shift, a common work schedule in 24-hour production companies has been posing some after-effects on workers’ health, ranging from physical to psychological, and lack of response to these effects could result in cognitive deficiencies for workers and increased downtime for organisations. The objective of this study is to evaluate the effect of the night shift on the response time of workers to digital visual stimuli as compared to the day shift. Twenty-two shift operators from a bottling line between the ages of 25 and 35 years were subjected to psychomotor vigilance test (PVT) using an android PVT application (Versor-PVT Version 1.03) to assess their response times to visual stimuli and analysed using the SPSS software to determine the data distribution, skewness, and kurtosis. Based on the determined data distribution, Wilcoxon signed rank test (WSRT) was utilised to determine the level of significance of the differences between the two of them. The recorded minimum and maximum average response times for post-day and post-night shifts respectively were: 609.94 ms and 733.64 ms; 644.56 ms and 944.17 ms. Results clearly showed that night shift has significant negative impact on the response time of tested operators, such as delayed ability to respond to situations, including fault rectification, thus causing safety concern, and reducing productivity. In conclusion, additional cost is imminently incurred on the part of the organisation in settling medical bills and compensations. The WSRT analysis indicated that there is 95% probability of generating similar results on repeating the experiment under same conditions.